Influence of the Formulation on the in vitro Transdermal Penetration of Sodium Diclofenac - Calpenaa, Ana C.; Escribanoa, Elvira; Martina, Helena San; Laurobaa, Jacinto; Obach, Rosendo; Domenecha, Jose (Arzneimittelforschung, 1999)
A study on the transdermal permeation through human skin was performed with a series of 6 semisolid formulations (A−F) containing 1% sodium diclofenac (CAS 15307-79-6) (w/w). A commercially available drug preparation was tested as a reference. Based on permeation characteristics, a study on the topical and systemic anti-inflammatory activities of three formulations (A, F and the reference formulation) was conducted using the model of erythema induced by UV radiation in hairless rats. This is expected, together with the index of topical anti-inflammatory activity to allow the selection of the most suitable formulation for dermal application.The following representative parameters were measured in the permeation study: amount of diclo- fenac permeated at 24 h, flow, lag time and amount of drug retained in skin at 24 h. Of the formula- tions tested, diclofenac formulated in the reference formulation showed the highest values of amount of diclofenac permeated at 24 h, amount of drug retained in skin at 24 and flow. As regards the skin inflammation test, no significant differences (p < 0.05) are seen between the topical and systemic anti-inflammatory activities of the three formulations tested. However, in absolute value, formulation F shows a lower systemic activity, which would prevent potential side effects of diclofenac. Since the topical anti-inflammatory index obtained for this formulation was > 1, it is concluded that a good therapeutic performance could be obtained in the treatment of local inflammation with diclofenac by using formulation F.
Keywords: CAS 15307-79-6; Diclofenac, percutaneous penetration; pharmacological activity, topical formulations